2010
DOI: 10.5155/eurjchem.1.3.206-210.128
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of natural color component from the bark of Belleric myrobalan (Terminalia bellerica): Kinetic and adsorption studies

Abstract: KEYWORDSBaicalein, a trihydroxy flavone from the bark of Terminalia bellerica was identified as a natural colorant. The potential of the natural color component on silk yarn was tested. Its properties of color fastness with regard to light, washing and crocking were investigated and found to be satisfactory. Thermodynamic parameters were evaluated. The positive value of enthalpy of dyeing suggests the endothermic nature of dyeing and the negative entropy implies that the dye molecules are orderly arranged on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The changes in colour depth vs light fastness grades in dyeings mordanted with aluminium (), tin (), iron (), chromium (), and copper () salts . Quadrants are indicated by Roman numerals in part (a) of the figure.…”
Section: Colour Depth Changes and Light Fastness Improvementsmentioning
confidence: 99%
See 2 more Smart Citations
“…The changes in colour depth vs light fastness grades in dyeings mordanted with aluminium (), tin (), iron (), chromium (), and copper () salts . Quadrants are indicated by Roman numerals in part (a) of the figure.…”
Section: Colour Depth Changes and Light Fastness Improvementsmentioning
confidence: 99%
“…The changes in colour (lightness, brightness, and hue) vs light fastness grades in dyeings mordanted with aluminium (), tin (), iron (), chromium (), and copper () salts …”
Section: Colour Changes and Light Fastness Improvementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mongkholrattanasit et al [6] and Goodarzian & Ekrami [13] reported that dyes extracted from Eucalyptus leaves and Rubia Tictorium L. showed wash fatsness for change in colour and staining is 4/5. K. N. Vinod [7] stated that dyes from bark of Terminalia bellerica showed wash fastness to staining between 4 -5. Colour fastness values for staining of our study are comparable with data reported by these researchers.…”
Section: Colourfastness To Washingmentioning
confidence: 99%
“…using naturally occurring sources of dye) maintain that natural dyes have a far superior aesthetic quality, which is much more pleasing to the eye [4]. There are also some studies regarding producing natural dyes such as dyes extracted from red prickly pear [5], eucalyptus leaves [6], Terminalia bellerica (T. bellerica) [7] and many more.…”
Section: Introductionmentioning
confidence: 99%